Shifting The Relationship Between Market Sentiment, Market Volume, Trading Volume and Volatility on The Indonesia Stock Exchange Approach Model Vector Autoregression - Mariyani, Dede; Hariyanti, Hariyanti; Kalista, Anggian (Eduvest - Journal of Universal Studies, 2025)
This study analyzes the relationship between market sentiment, trading volume, and stock volatility on the Indonesia Stock Exchange (IDX) using the Vector Autoregression (VAR) model. The research addresses the complexity of these interdependent variables and their impact on market dynamics, aiming to provide insights for investors, regulators, and policymakers. The objective was to evaluate how changes in market sentiment affect trading volume and stock volatility and how these variables interact over time. The VAR model was applied to daily and weekly data on market sentiment, trading volume, and stock volatility from IDX. Results indicate that positive sentiment generally increases trading volume and stock volatility, while negative sentiment tends to reduce trading activity and escalate volatility. The findings also highlight the significant role of market liquidity, as trading volume impacts volatility by improving market stability. This study underscores the importance of sentiment analysis in investment strategies and market regulation, suggesting that maintaining market liquidity and stabilizing sentiment can enhance market efficiency and stability. The implications of these results are critical for improving risk management and informing investment decisions in the Indonesian capital market.